Analysis of bone mineral profile and TSH in early non-dialysis stages of chronic kidney disease - a retrospective cross-sectional study - Immaculate Rithika Rajan; Karthick Elango; Sathya Selvarajan (Universitas Nahdlatul Ulama Surabaya, 2024)
The objective of this study is to analyse the levels of Thyroid stimulating hormone (TSH) and the Bone Mineral Profile (Vitamin D, Parathyroid hormone (PTH), calcium, phosphorus, magnesium, and alkaline phosphatase [ALP]) levels in the early stages of chronic kidney disease (CKD) based on Glomerular filtration rate (GFR). A retrospective analysis was conducted involving 247 CKD patients admitted to the nephrology department at Sri Ramachandra Medical College Hospital from January to June 2022. The estimated GFR (eGFR) was calculated utilizing the CKD-EPI formula provided by the National Kidney Foundation. All biomarkers were analysed using automated platforms. The baseline ages for the three groups were 52.5, 68, and 66.5 years respectively (p<0.001). The comparative analysis revealed statistically significant differences solely among Vitamin D, creatinine, PTH, and phosphorus across the three groups. Further correlation analysis demonstrated changes in bore significant correlations with only creatinine, vitamin D, and PTH. This study concludes that in the early stages of CKD, vitamin D followed by PTH appears to be the earliest biomarker for assessing CKD-Mineral and Bone Disorder (CKD-MBD) occurring prior to any alterations in calcium and phosphate levels. As such, early consideration of supplementation may prove beneficial in mitigating disease progression and preventing cardiovascular complications.